Fermented was reported to have different physicochemical and functional properties to those of non fermented flour. The objective of this research was to study the effect of spontaneous fermentation to chemical and rheological properties of corn flour and to identifying correlation among parameters. Flour was prepared by spontaneous fermentation with variation of fermentation time (0, 12, 24, 36, 48, 60 and 72 hours). The result indicated that the increasing of corn grits fermentation time wa - Nur Aini; Purwiyatno Hariyadi; Tien R. Muchtadi; Nuri Andarwulan (Forum Pasca Sarjana, 2009)
Fermented was reported to have different physicochemical and functional properties to those of non fermented flour. The objective of this research was to study the effect of spontaneous fermentation to chemical and rheological properties of corn flour and to identifying correlation among parameters. Flour was prepared by spontaneous fermentation with variation of fermentation time (0, 12, 24, 36, 48, 60 and 72 hours). The result indicated that the increasing of corn grits fermentation time was decrease of protein, crude fiber, lipid, ash, starch and amylase content of corn flour. The increasing of protein content, reduction sugar, crude fiber, ash, bulk density and gelatinization time were decrease of gel strength. Gel strength will be promote with increasing of angle of repose and peak viscosity. Gel stickeness will decrease with increasing of amylosa: amylopecyin ratio and breakdown viscosity. Key words: white corn, flour,fermentation, chemical, rheological